Responsible Investment and Sustainability: Systematic Literature Review - Marwane , Boussetta; Mariame , Ababou; Sanaa , Faquir (International Journal of Accounting and Economics Studies, 2025)
This systematic literature review explores how environmental information influences investment decisions and financial performance within responsible investment (RI). Analyzing 39 key articles reveals RI's potential to drive environmental change and contribute to long-term sustainability goals.Companies are disclosing more ESG (environmental, social, and governance) information due to investor pressure and the value of transparency. Investor behavior is influenced by ESG data, but concerns about greenwashing and social movements can also impact choices. Strong corporate governance is crucial for fostering robust ESG practices.The review highlights the need for standardized ESG metrics, long-term impact studies of RI, and greenwashing mitigation strategies. It also emphasizes exploring social and governance aspects of ESG and promoting RI in developing economies. By addressing these areas, stakeholders can collaborate to maximize RI's positive impact and build a more sustainable future.
Keywords: Decision-Making, Environmental Information, Financial Performance, Responsible Investment, Sustainable Development